Nickel–copper hybrid electrodes self-adhered onto a silicon wafer by supersonic cold-spray. (July 2015) - Lee, Jong-Gun; Kim, Do-Yeon; Kang, Byungjun; Kim, Donghwan; Song, Hee-eun; Kim, Jooyoung; Jung, Woonsuk; Lee, Dukhaeng; Al-Deyab, Salem S.; James, Scott C.; Yoon, Sam S.
Graphical abstract: Abstract: High-performance electrodes are fabricated through supersonic spraying of nickel and copper particles. These electrodes yield low specific resistivities, comparable to electrodes produced by screen-printed silver paste and light-induced plating. The appeal of this fabrication method is the low cost of copper and large area scalability of supersonic spray-coating techniques. The copper and nickel electrode was fabricated in the open air without any pre- or post-treatment. The spray-coated copper–nickel electrode was characterized by optical microscopy, scanning electron microscopy (SEM), transmission electron microscopy (TEM), X-ray diffraction, and energy dispersive spectroscopy. Although both SEM and TEM images confirmed voids trapped between flattened particles in the fabricated electrode, this electrode's resistivity was order 10 −6 Ω cm, which is comparable to the bulk value for pure copper.